On the Speed of Convergence in Endogenous Growth Models - Ortigueira, Salvador; Santos, Manuel S. (American Economic Review, 1997)
In this paper we analyze the speed of convergence to a balanced path in a class of endogenous growth models with physical and human capital. We show that such rate depends locally on the technological parameters of the model, but does not depend on preferences parameters. This result stands in sharp contrast with that of the one-sector neoclassical growth model, where both preferences and technologies determine the speed of convergence to a steady-state growth path.